Implementation of SCADA with Improvement of DKI Jakarta Flood Control Monitoring System - Ramza, Harry; Adianto, Alfret; Roza, Emilia; Siregar, Masbah Rotuanta Tagore; Sofwan, Agus (TIME in Physics, 2024)
SCADA (Supervisory Control and Data Acquisition) is a system that can supervise, control and acquire data on a plant. This system uses a computer to display the status of sensors and actuators in a plant, display them in graphical form and store them in a database. Generally, this computer is connected to a Programmable Logic Control (PLC) controller through a certain communication protocol (serial communication). This Engineering Practice Report discusses the improvement of the Jakarta flood control monitoring system uses the SCADA system where currently the use of SCADA is only limited to the visual monitoring display of CCTV cameras with water level elevation notifications and risk level indicators arising from the data received. In the design of the SCADA system in pump houses or flood pump sub-polders in locations spread throughout DKI Jakarta that exist today, especially in the current projects implemented, namely JGC Marunda Sub Polder, Adyaksa Pump House and Tipala Pump House.